PENGARUH PRAKTIK MANAJEMEN SDM TERHADAP KINERJA KARYAWAN DENGAN KETERLIBATAN KARYAWAN DAN KEPUASAN KERJA SEBAGAI PEMEDIASI (STUDI PADA KARYAWAN PT DAN LIRIS SUKOHARJO) - Satria Yudha Pratama; Jati Waskito (POLITEKNIK LP3I JAKARTA, 2025)
Every company requires high-quality human resources to achieve the best results. Therefore, companies need to implement HRM practices that positively influence employees' attitudes. This research highlights the importance of effective human resource management in improving both individual and organizational performance. The study aims to analyze the impact of HRM practices on employee performance, with employee engagement and job satisfaction as mediators, among employees at PT Dan Liris Sukoharjo. Data were collected from 114 respondents using surveys and analyzed using quantitative methods with SEM PLS 3. The results show that HRM practices significantly affect employee engagement, job satisfaction, and employee performance. Job satisfaction proved to be a significant mediator, while employee engagement did not have a significant mediating effect. These findings suggest that focusing on job satisfaction is more effective in improving performance. The implications of this research emphasize the need for HR strategies that prioritize job satisfaction through a conducive environment, fair rewards, and career opportunities to achieve optimal employee and organizational performance.